Condições de trabalho e permanência docente no Programa de Ensino Integral (PEI) à luz da teoria de Pierre Bourdieu - Tassoni, Raquel Franco (Universidade Federal de São Carlos, 2026)
This dissertation analyzes the processes of adaptation and permanence of teachers in schools participating in the Programa de Ensino Integral (PEI) of the state of São Paulo, seeking to understand how the institutional and organizational dynamics of this program affect teachers’ working conditions, their permanence in the program, and their relationship with school culture, in light of Pierre Bourdieu’s theoretical framework. The study is situated within the context of the expansion of full-time education in Brazil, driven by national and international public policies, and the rapid growth of the PEI since 2012, strongly inspired by managerial and corporate models. A qualitative methodology was adopted, structured in three complementary stages: a systematic literature review, documentary analysis of official regulations and guidelines, and field research through questionnaires administered to teachers working in the PEI. The data were triangulated, resulting in three analytical axes: (a) teacher profile, characterization, and entry into the PEI; (b) institutional demands, management, and working conditions; and (c) conditions for permanence in the PEI. The results indicate that the accelerated expansion of the PEI has generated challenges in everyday school life, such as task overload, intensification of working hours, institutionalized surveillance, and tensions in teachers’ processes of adaptation and permanence, especially in more socially vulnerable school contexts. It was found that meritocratic logics and evaluation mechanisms operate as forms of symbolic distinction, reinforcing internal hierarchies and weakening professional bonds. Furthermore, adherence to the program is strongly conditioned by teachers’ capacity to adapt to the institutional habitus imposed by the PEI, contributing to feelings of instability, exclusion, or non-belonging. It is concluded that, although the PEI promotes a discourse of teacher valorization and pedagogical innovation, its practices reveal structural contradictions that directly affect teachers’ permanence. The strained processes of adaptation and permanence thus emerge as expressions of a policy that combines quantitative expansion with mechanisms of control and individual accountability, often disconnected from concrete working conditions. This study contributes to the critical debate on full-time education policies in Brazil and their effects on the educational field, highlighting the need for more democratic, participatory models that are coherent with the historical principles of integral education.
Working conditions and teacher continuity in the Programa de Ensino Integral (PEI) through the lens of Pierre Bourdieu's theory
Keywords: Programa de Ensino Integral (PEI); Trabalho Docente; Educação Integral; Pierre Bourdieu; Gestão Escolar; Teaching work; Integral Education; School Management; CIENCIAS HUMANAS::SOCIOLOGIA::FUNDAMENTOS DA SOCIOLOGIA; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; 4. Educação de Qualidade